Aplikasi Kombinasi Decanter solid dan Pupuk NPK Terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays saccharata Sturt) Pada Lahan Ultisol - Meri Apriani; Irianto Irianto; Dedy Antony (Universitas Batanghari, 2026)
Increasing sweet corn production faces several obstacles, especially those related to limited productive land, so it must utilize marginal land such as ultisols. To overcome the problem of low ultisol productivity, improvement through the use of organic and inorganic fertilizers is very important to improve the physical, chemical, and biological properties of the soil. This research was conducted in Penegah Village, Pelawan District, Sarolangun Regency, Jambi Province, at an altitude of ± 64 m above sea level and ultisol soil type, from July 2025 to September 2025. The research design used was a Randomized Block Design (RB) with a combination of solid decanter fertilizer treatment with NPK. The variables observed included solid decanter analysis, plant height, number of leaves, total leaf area, stem diameter, cob diameter, cob length, cob weight and sweetness level of corn fruit. Data were analyzed using analysis of variance, the data were first tested for normality, then continued with Duncan's Multiple Range Test (DMRT) at the α level = 5%. The research results showed that a combination of 15–20 tons ha⁻¹ of solid decanter fertilizer combined with 150–200 kg ha⁻¹ of NPK was the best treatment on Ultisol soils. This combination was able to produce optimal plant growth and support the formation of full cobs better than other treatments.